Knowledge and Practice of Infection Control in Impression Making among the Dental Health Care Professionals - Shrestha, Suraksha; Thakur, Smriti Narayan; Dulal, Najma (Journal of College of Medical Sciences-Nepal, 2019)
Background: Infection control is an imperative issue in the dental practice. Almost all of the dental procedures involve dealing with the saliva, blood and oral fluids which may have sufficient pathogens and cause cross infection through contaminated instruments, materials and surfaces. Therefore the dental health care workers must be aware of the possible contamination and should follow the measures to prevent it. The aim of the study is to assess the knowledge of dental health care professionals regarding infection control and modes of infection control employed by them during one of the dental procedure i.e. impression making. Methods: A self-assessment questionnaire based survey was carried out among dental health care professionals to assess the knowledge and practice of infection control in dental clinics. Survey instruments containing 14 questions were randomly distributed to 113 dental health care professionals regarding knowledge of infection control methods and infection control practice during impression making in dental clinics and hospitals. Data was collected and analyzed. Results: Though most of the health care professionals (88.6 %) think an impression taken from patient mouth will have enough pathogens to cause cross infection, our study showed that only 52.3 % of them disinfect all the impression and washing impression under running water was the method used for disinfection by the majority (78.9 %). Conclusions: The knowledge about infection control during impression making is better among the dental health care professionals. But there is a need to improve the practice to minimize cross infection in dental set up and reduce the associated morbidity and mortality rates for both dental practitioners themselves and patients.